Quick-cooking laminated white salted noodle development. (March 2023) - Soncin Alfaro, Gabriely M.; Kiszonas, Alecia M.; Morris, Craig F.
Abstract: The amylose/amylopectin ratio in starch influences flour pasting properties and thus food applications. Using waxy wheat flour to reduce the amylose content in white salted noodles increases cohesiveness; however, 100% full waxy results in undesirable high softness. This study developed a novel quick-cooking fresh white salted noodle by combining the pasting characteristics of full waxy and the texture of normal starch profile wheat in a three-layer laminated noodle. Flour from wheat varieties Otto (normal starch), Ryan (partial waxy), and USDA Lori (full waxy) were used. The impact of the new formula and process on noodle quality was compared with samples made from commercial flour using approved methods. The three-layer laminated noodles with outer layers of normal starch and inner layer of waxy wheat cooked faster (8min 30s; P  < 0.0001) than regular or three-layer commercial flour noodles (10min 30s). The combination of normal-starch and full waxy wheat produced laminated noodles with lower cooking time, similar cooking loss, slightly firmer texture, and lower water absorption than noodles made with commercial flour. With noodles being a staple food in many Asian countries and increased consumption in other regions of the world, this novel three-layer laminated noodle is a time-saving new application for waxy wheat. Graphical abstract: Image 1 Highlights: White salted noodles were made by combining different starch profile layers. Quality of laminated noodles was compared with standard commercial noodles. Laminated noodles had similar cooking loss and brightness compared to standards. Laminated noodles with waxy inner layer cooked ∼20% faster than commercial noodles.